2017
DOI: 10.3906/tar-1701-124
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Trichogramma evanescens and Bacillus thuringiensis var. kurstakiin control of Cydia pomonella (L.) in Turkey

Abstract: This study was conducted to evaluate the effectiveness of Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae) release with as well as without Bacillus thuringiensis var. kurstaki (Berliner) in biological control of Cydia pomonella (L.) (Lepidoptera: Tortricidae) in the Galaxy Gala apple variety grafted onto M9 rootstock in 2016. Four treatments were analyzed: releasing T. evanescens alone (TE), applying B. thuringiensis var. kurstaki (BT) alone, applying both (TE + BT), and a control (C) without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…An important aspect of horticulture is the cultivation of plants for food, fiber, biofuel, medicine and other products used to sustain and enhance human life . A variety of protection and defense systems are implemented during the growth and developmental processes of plants to resist the stresses of drought, salinity, environmental pollution, pests and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of horticulture is the cultivation of plants for food, fiber, biofuel, medicine and other products used to sustain and enhance human life . A variety of protection and defense systems are implemented during the growth and developmental processes of plants to resist the stresses of drought, salinity, environmental pollution, pests and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…AlSaedi et al [34] reported that B. thuringiensis was not harmful for the parasitoids as proven by the highest parasitism rates of two species of Trichogramma parasitoids on Tuta absoluta infesting tomato in greenhouse. T. evanescens was highly effective on suppressing the Cydia pomonella (L.) in apple plantations when the parasitoid releases were combined with B. thuringiensis than either of the agents being used alone [35][36][37]. The results from the current study revealed that B. thuringiensis had no adverse effect on Trichogramma.…”
Section: Parasitism Percentagementioning
confidence: 54%
“…The codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae) is serious pest of apple fruits. Larvae feed on the fruit directly, creating spiral galleries towards the seed chamber of fruit and severely effects quality of fruit by feeding in the mesocarp of the apple and in the kernel (Beers et al, 2003;Öztemiz et al, 2017). Without any plant protection measures, damage may reach 60-95% of apple production (Kuyulu and Genç, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been known as important pest, several studies have been conducted related to its distribution (Jiang et al, 2018), genetic structure (Meraner et al, 2008;Men et al, 2013), insecticide resistance (İşçi and Ay, 2017;Bosch et al, 2018), biological control (Öztemiz et al, 2017;Sigsgaard et al, 2017), mating disruption (Kovanci, 2015;McGhee et al, 2016), and field studies (Pajač et al, 2012;Blomefield and Gliomee, 2012).…”
Section: Introductionmentioning
confidence: 99%